Consolidation centers strategy for the distribution of prickly pear in Mexico - Granillo Macias, Rafael; Gonzalez Hernandez, Isidro Jesus; Santana Robles, Francisca; Martinez Flores, Jose Luis (Revista Mexicana de Ciencias Agrícolas, 2019)
The cultivation of the prickly pear (Opuntia spp.) has positioned Mexico as the world leader in the production of this agri-food product. Because the harvest is sent to different markets throughout the country, distribution and marketing operations represent a challenge in this supply chain. This research was conducted based on the national production obtained in 2016, with the objective of developing a distribution network that maximizes the profits of the producers. The hypothesis was that based on a consolidation center strategy, it is possible to design a model for a distribution network that selects optimal routes based on transport costs and sales prices in the demanding markets. Mixed integer linear programming with continuous variables was used to determine the quantities of products to send and integer variables to select the consolidation centers. The proposed model was implemented; through, an algorithm programmed in Matlab which applies mathematical optimization techniques to evaluate the best feasible solution. The results indicate that four consolidation centers should be used in the state of Guanajuato, ten in Zacatecas, one in Hidalgo and Puebla respectively, two in the State of Mexico and six in San Luis Potosí. With this proposal, the state of Zacatecas concentrates at least 50% of the harvest, so this location is key to optimize the profit in the supply chain of the prickly pear.
Keywords: Opuntia spp.; consolidation centers; logistics network; mixed whole linear programming; optimization